2010
DOI: 10.1111/j.1574-0862.2010.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Cotton market integration and the impact of China's new exchange rate regime

Abstract: This article studies the integration of China's cotton market with the international market, especially the U.S. market. Investigating the futures prices from the Intercontinental Exchange (ICE) in the U.S. and the Zhengzhou Commodity Exchange (ZCE) in China with several time series models, we find that a long-run cointegration relationship exists between these two series. The two markets share price transmissions, and based on results from an Autoregressive Conditional Heteroskedasticity (ARCH) model, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…Miljkovic (2009) considers that, due to import bans, Canadian and U.S. livestock prices can be either integrated or separated from 1996 to 2004, and that high trade dependency of prices would cause fragility and prices would be more vulnerable to exogenous shocks that reduce trade flows. Ge, Wang, and Ahn (2010) test the integration relationship of China's cotton market with the international market, especially the United States, and find that a long-run integration relationship exists, and that price hostilities are similar. Furthermore, they assess for the first time the impact of a market-oriented exchange rate system on cotton futures prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Miljkovic (2009) considers that, due to import bans, Canadian and U.S. livestock prices can be either integrated or separated from 1996 to 2004, and that high trade dependency of prices would cause fragility and prices would be more vulnerable to exogenous shocks that reduce trade flows. Ge, Wang, and Ahn (2010) test the integration relationship of China's cotton market with the international market, especially the United States, and find that a long-run integration relationship exists, and that price hostilities are similar. Furthermore, they assess for the first time the impact of a market-oriented exchange rate system on cotton futures prices.…”
Section: Literature Reviewmentioning
confidence: 99%
“…4 Researchers have examined the impact of Bt cotton adoption in China on global cotton trade (Anderson, Valenzuela, and Jackson, 2008;Fang and Babcock, 2003;Frisvold, Reeves, and Tronstad, 2006;Huang et al, 2004). Others have examined the effects of China's currency policy on global cotton markets (Ge, Wang, and Ahn, 2010;Pan et al, 2007), how the elimination of the Multi-Fiber Agreement affected China's role in global cotton markets (Audet, 2007;Li, Mohanty, and Pan, 2005;MacDonald et al, 2010;Mutuc et al, 2011), and how China's WTO accession affected global cotton trade (Fang and Babcock, 2003;Fuller et al, 2003). A recent study has also considered the global recession and China's cotton supply chain (Xiao, 2010).…”
mentioning
confidence: 99%
“…Regarding cotton supply chains, research has shown that international cotton markets are well‐integrated (Baffes and Ajwad, ; Ge et al., ; Mutuc et al., ). However, evidence of integration between farm gate and international markets has been mixed.…”
Section: Literature Reviewmentioning
confidence: 99%